Economic and Strategic Implications of Privatization in Pakistan: Case Study of Pakistan Steel Mill - Zubair, Muhammad; Wizarat, Shahida; Imran, Kashif (Pakistan Journal of Economic Studies (PJES), 2022)
Privatization started in the 1980s in Pakistan, but it failed to turn state-owned enterprises into profitable entities, improve efficiency, ensure better governance, retire debt, and fix the fiscal balancing problem. Privatization in Pakistan seems to be politically conditioned and externally imposed rather than fulfilling domestic economic needs. This study aims to evaluate the privatization process in Pakistan descriptively; hence, the economic, political, and strategic implications of privatization in Pakistan are discussed. Pakistan Steel is an important entity in the engineering industry, significant in its economic, social, and strategic contributions. This study also explains the after-privatization implications of the Pakistan Steel Mill, Pakistan’s economic and strategic asset.